Manda brasa: a variação do imperativo gramatical no falar Maranhense - LOPES, Matheus da Silva (2023)
This research is a clipping of the linguistic reality in the state of Maranhão, which has as its theme the variation of imperative sentences. Through data collected by the Linguistic Atlas of Maranhão Project - ALiMA, we sought to investigate the variation in the imperative mood used in the construction of sentences in Portuguese: the true imperative and the supplementary imperative (Scherre, 2007). In light of the theories of Dialectology and Sociolinguistics, represented here by Cardoso (2010), Labov (2008 [1972]), Scherre et al (2007), among others, we aimed to map the variation of imperative sentences in Maranhão, considering social variables and language. The data collection and analysis methodology follow the paths traced by the ALiMA and VarSint projects, the first being the database from which the corpus was extracted and the second the research project with which this study establishes a theoreticalmethodological and practical interface, to which the study is linked. The research involves five municipalities in Maranhão, namely: Alto Parnaíba, Bacabal, Caxias, Imperatriz and São Luís. The latter, the state capital, deserves special attention due to the number of informants and the division into two distinct schooling levels, unlike the other locations. The results show that the state of Maranhão mostly uses the true imperative, given the significant number of sentences with this form in the corpus. Based on statistical rounds carried out in the GoldVarb X program, we found that the diassexual, diastratic and sentence polarity variables are the ones that most influence the investigated phenomenon. In this way, the study undertaken by us represents another step in the representation of the state within the national panorama of research on linguistic variation and can serve as a basis for future investigations on the same topic.